2021
DOI: 10.3389/fnhum.2021.641273
|View full text |Cite
|
Sign up to set email alerts
|

Magnetoencephalography Responses to Unpredictable and Predictable Rare Somatosensory Stimuli in Healthy Adult Humans

Abstract: Mismatch brain responses to unpredicted rare stimuli are suggested to be a neural indicator of prediction error, but this has rarely been studied in the somatosensory modality. Here, we investigated how the brain responds to unpredictable and predictable rare events. Magnetoencephalography responses were measured in adults frequently presented with somatosensory stimuli (FRE) that were occasionally replaced by two consecutively presented rare stimuli [unpredictable rare stimulus (UR) and predictable rare stimu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 73 publications
0
4
0
Order By: Relevance
“…In addition to location deviance sMMR (e.g., Akatsuka et al, 2007; Chen, Hämmerer, D’Ostilio, et al, 2014; Hautasaari et al, 2019; Kekoni et al, 1997; Naeije et al, 2016, 2018; Restuccia et al, 2007; Restuccia et al, 2009; Shen, Smyk, et al, 2018; Shen, Weiss, et al, 2018; Shinozaki et al, 1998; Strömmer et al, 2014; Strömmer et al, 2017; Tarkka et al, 2016; Xu et al, 2021), a somatosensory mismatch response has been demonstrated in an ignore condition by changes in various other stimulus properties, such as duration (Butler et al, 2011; Chen, Hämmerer, D’Ostilio, et al, 2014, Chen et al, 2018; Spackman et al, 2007; Spackman et al, 2010), vibratory frequency (Kekoni et al, 1997; Spackman et al, 2007), and a within-pair inter-stimulus interval of stimulus pairs (Akatsuka et al, 2005) that are not related to spatial location or the somatotopic organization of SI. Therefore, the present findings concerning the differences between MMR to somatosensory location deviance (existing) and intensity deviance (no significant response found) should not be explained only by the difference of how these stimulus features recruit the cortical somatotopy of fingers.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In addition to location deviance sMMR (e.g., Akatsuka et al, 2007; Chen, Hämmerer, D’Ostilio, et al, 2014; Hautasaari et al, 2019; Kekoni et al, 1997; Naeije et al, 2016, 2018; Restuccia et al, 2007; Restuccia et al, 2009; Shen, Smyk, et al, 2018; Shen, Weiss, et al, 2018; Shinozaki et al, 1998; Strömmer et al, 2014; Strömmer et al, 2017; Tarkka et al, 2016; Xu et al, 2021), a somatosensory mismatch response has been demonstrated in an ignore condition by changes in various other stimulus properties, such as duration (Butler et al, 2011; Chen, Hämmerer, D’Ostilio, et al, 2014, Chen et al, 2018; Spackman et al, 2007; Spackman et al, 2010), vibratory frequency (Kekoni et al, 1997; Spackman et al, 2007), and a within-pair inter-stimulus interval of stimulus pairs (Akatsuka et al, 2005) that are not related to spatial location or the somatotopic organization of SI. Therefore, the present findings concerning the differences between MMR to somatosensory location deviance (existing) and intensity deviance (no significant response found) should not be explained only by the difference of how these stimulus features recruit the cortical somatotopy of fingers.…”
Section: Discussionmentioning
confidence: 99%
“…This is important because the physical features of the stimuli most likely significantly affect the responses. Quite surprisingly, most previous studies have not taken into account this either in the study design or in the analysis (see, however, Xu et al, 2021; Ostwald et al, 2012 for somatosensory deviance detection responses).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations